Estudio de Pre factibilidad para la creación de empresa productora de abono orgánico, obtenido por compostaje en el municipio de Santa Rosa, Boyacá (2023)
The prefeasibility study aims to analyze the viability of implementing a company dedicated to the manufacture of organic composted fertilizer in the province of Tundama in the department of Boyacá, the production plant will be established in the Municipality of Santa Rosa de Viterbo. For the corresponding analyses, field information has been collected through surveys directed at agricultural producers located in the different municipalities of the province regarding the use of organic fertilizers. The results show the feasibility of project implementation in different aspects such as the evaluation of environmental impacts and financial profitability.